Efektivitas Berbagai Konsentrasi Infusa Daun Salam (Eugenia polyantha Wight) terhadap Daya Antibakteri Staphylococcus aureus Secara In Vitro - Apriani, Dewi; Amaliawati, Nur; Kurniati, Eni (POLTEKKES KEMENKES YOGYAKARTA, 2014)
Staphylococcus aureus is one of the acne-causing bacterias. Chemical compound in the Bay leaves are well-known as an antibacterial agent to inhibit the growth of Staphylococcus aureus. This study aimed to determine the influence of various Bay leaf (Eugenia polyantha Wight) infusing concentration toward the inhibition of Staphylococcus aureus growth. This research is experimental study with post-test and control group design. The sensitivity test methods toward Staphylococcus aureus were divided into five groups of bay leaf infusing concentration of 60%, 70%, 80%, 90%, and 100%. This method are used in 6 times to obtained 30 datas. Then, the datas were analyzed descriptively and analytically by ANOVA using SPSS 16.0 for Windows. The infusion of Bay leaves had inhibition activity against Staphylococcus aureus growth based on ANOVA test which showed a significance value 0.000 <0.05. There was a proof that the infusion of Bay leave have an effect to inhibit the growth of Staphylococcus aureus.